Dinamika Loyalitas Pelanggan Produk Berbahan Dasar Plastik: Peran Mediasi Kepuasan Pelanggan - Christofer, Andrew; Keni, Keni (Universitas Bunda Mulia, 2025)
Consumption of plastic-based products always has its own dynamics as it faces issue regarding its impact to environment, thereby companies are adapting by offering eco-friendly plastic-based products as an attempt to retain customers. Therefore, this study aims to examine the impact of price perception, product quality, and social influence on customer satisfaction and loyalty toward plastic-based products in Jakarta. Additionally, this study investigates the mediating role of customer satisfaction in the relationships between product quality, price perception, social influence, and customer loyalty. The sample of this study is 180 users of a plastic-based product brand in Jakarta. Data were collected by using convenience sampling through Google Forms. The data were analyzed by using SEM-PLS method through SmartPLS 4 software. This study revealed that product quality, price perception, and social influence significantly affect customer satisfaction. Moreover, product quality and social influence directly affect customer loyalty. However, price perception doesn’t directly influence customer loyalty but does so indirectly through customer satisfaction. This study also highlights the crucial role of customer satisfaction in mediating the influence of product quality and social influence toward loyalty. These findings provide strategic insights for companies aiming to enhance customer loyalty by focusing on product quality, social influences, and optimizing customer satisfaction.